Vortioxetine treatment for neuropathic pain in major depressive disorder: a three-month prospective study - Eliaçık, Sinan; Erdogan Kaya, Ayse (Frontiers in Neurology, 2024)
Introduction and objective Several studies revealed the therapeutic potential of vortioxetine (Vo) for pain. In this context, we aimed to evaluate the efficacy of Vo as a safe and tolerable novel pharmacologic agent in treating neuropathic pain (NP) in patients with major depressive disorder (MDD). Materials and methods The population of this cross-sectional prospective study consisted of all consecutive patients who were newly diagnosed with MDD by a neurology doctor at a psychiatric clinic and had NP for at least 6 months. All patients included in the sample were started on Vo treatment at 10 mg/day. They were assessed with Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Self-Reported Leeds Assessment of Neuropathic Symptoms and Signs (S-LANSS), Douleur Neuropathique 4 Questions (DN4), Montreal Cognitive Assessment (MoCA), and Neuropathic Pain Impact on Quality of Life (NePIQoL) at the beginning of treatment and during the follow visits conducted at the end of the first, second and third months of the treatment. During these follow-up visits, patients were also queried about any side effects of Vo. Results The mean age of 50 patients included in the sample, 76% of whom were female, was 45.8 ± 11.2 years. There was a significant reduction in patients’ NP complaints based on DN4 and S-LANNS, the subscales of NePIQoL, and significant improvement in MoCA. There was a significant reduction in patients’ NP complaints based on DN4 and S-LANNS scores and a significant improvement in scores of the subscales of NePIQoL and MoCA. Conclusion The study’s findings indicate that Vo, with its multiple mechanisms of action, can effectively treat NP independently of its mood-stabilizing effect. Future indication studies for Vo are needed to establish Vo’s efficacy in treating NP.